Induced spoofing detection method based on error valuation accumulation open-loop correction - Lunlong ZHONG; Jiongpo LIU; Yongyu LIU (Dianxin kexue)
Induced satellite spoofing interference can induce the aircraft to gradually deviate from the predetermined trajectory, and it is difficult to detect.So timely and effective detection of interference is the guarantee of flight safety.Based on the existing tightly integrated navigation system, an error valuation accumulation open-loop correction structure was designed.It was proved that the performance of the designed structure was equivalent to the performance of traditional tightly integrated navigation system with closed-loop correction.On the basis of designed structure, combining the tightly integrated navigation system with the adaptive sequential probability ratio test method, an induced spoofing detection method based on the error valuation accumulation open-loop correction was proposed.A spoofing detection statistic for induced spoofing detection was constructed by integrating the tightly integrated navigation information with other navigation information that was not affected by spoofing interference.Simulation results show that the designed open-loop correction structure can avoid the divergence problem of the integrated navigation filter caused by the inertial navigation system error accumulated over time.Moreover, the proposed spoofing detection method can improve the detection effect of the algorithm of the small induced spoofing under the “worst” case further.